Street names as the stuff of “banal patriotism” - Rutkowski , Mariusz (Papers in Linguistics, 2023)
M. Billig’s concept of banal nationalism (2008) assumes that nationalism can be strengthened primarily by “unnoticeable”, everyday practices and “hiding” big symbols in small, everyday things (flags, banknotes, anthems, etc.). Similarly, patriotism and national identity can also be shaped and strengthened through “everyday” and “unnoticeable” linguistic symbols: street names. These names are usually given in memory of distinguished, great people who are “models of patriotism” and belong to the national cultural canon. Such commemorative names are then reproduced in everyday communication practices when navigating urban spaces. The paper will show how names shape the patterns of Polish patriotism: what values are considered key to shaping the attitudes of modern Poles. Changes in the scope of this naming under the influence of political changes will also be shown. As a result, some names are erased from collective memory, while others are forcibly introduced into it, with the intention of thus forming an identity based on new values. Street names are therefore also an important tool of language policy and historical policy. The persuasive and memory-forming power of street names lies in their usability and a kind of “habituation”: names are part of everyday life, they are normal, natural, and thus – unnoticeable as a tool of politics and ideology. The methodological framework of the paper will be the author’s method of Onomastic Discourse Analysis.